Instrument Validation of Chemistry Learning Module with the Topic of Increasing Goat Weight for the Millennial Generation - K Anom W; Made Sukaryawan; Abdurachman Ibrahim; Eka Ad'hiya (Jurnal Penelitian Pendidikan IPA, 2023)
Module instrument validation plays an important role in ensuring the quality of the module. For this reason, the purpose of this study was to develop a valid instrument for the development of STEM-Integrated Chemistry Learning Module and chemically characterized Entrepreneurship Course for the millennial generation at Sriwijaya University’s Chemistry Education Study Program. The instrument includes content, pedagogy, and design or practicality validation, which is valid, practical, and effective for limited trials. The respondents of this study were semester-6 students and lecturers of Chemistry Education Study Program, Faculty of Teacher Training and Education, Sriwijaya University. The results of instrument validation by experts showed that the average Aiken coefficient value on material was 0.92, pedagogy 0.73, and practicality 0.74, which are in very high and high categories. The results indicated that the module development instrument has met the validity and practicality criteria